Quantitatively biomechanical response analysis of posterior musculature reconstruction in cervical single-door laminoplasty. (May 2023) - Liang, Z.; Xu, G.; Liu, T.; Zhong, Y.; Mo, F.; Li, Z.
Highlights: Classic and modified single-door laminoplasty models were developed and compared, which indicated the latter was superior to the former due to the posterior musculature reconstruction in restoring ROM and limiting the loading responses. All these were well correlated with a review of clinical data on laminoplasty scenarios. Analysis of the load concentration locations showed that the C2 muscle attachment sustained more tensile loading than the C7 muscle attachment. These tensile damping of the musculature reconstruction retained more postoperative cervical motion. Motion-sparing is beneficial for the recovery of postoperative neck movement and reducing the risk of eventual kyphosis and axial pain. Clinical relevance of this study indicated that surgeons are encouraged to make every effort to preserve the attachment of the C2 whenever feasible in laminoplasty. Abstract: Background and objective: The current trend of laminoplasty is developing toward the goal of muscle preservation and minimum tissue damage. Given this, muscle-preserving techniques in cervical single-door laminoplasty have been modified with protecting the spinous processes at the sites of C2 and/or C7 muscle attachment and reconstruct the posterior musculature in recent years. To date, no study has reported the effect of preserving the posterior musculature during the reconstruction. The purpose of this study is to quantitatively evaluate the biomechanical effect of multiple modified single-door laminoplasty procedures for restoring stability and reducing response level on the cervical spine. Methods: Different cervical laminoplasty models were established for evaluating kinematics and response simulations based on a detailed finite element (FE) head-neck active model (HNAM), including ① C3 – C7 laminoplasty (LP_C37), ② C3 – C6 laminoplasty with C7 spinous process preservation (LP_C36), ③ C3 laminectomy hybrid decompression with C4 – C6 laminoplasty (LT_C3 + LP_C46) and ④ C3 – C7 laminoplasty with unilateral musculature preservation (LP_C37 + UMP). The laminoplasty model was validated by the global range of motion (ROM) and percentage changes relative to the intact state. The C2 – T1 ROM, axial muscle tensile force, and stress/strain levels of functional spinal units were compared among the different laminoplasty groups. The obtained effects were further analysed by comparison with a review of clinical data on cervical laminoplasty scenarios. Results: Analysis of the locations of concentration of muscle load showed that the C2 muscle attachment sustained more tensile loading than the C7 muscle attachment, primarily in flexion-extension (FE) and in lateral bending (LB) and axial rotation (AR), respectively. Simulated results further quantified that LP_C36 primarily produced 10% decreases in LB and AR modes relative to LP_C37. Compared with LP_C36, LT_C3 + LP_C46 resulted in approximately 30% decreases in FE motion; LP C37 + UMP also showed a similar trend. Additionally, when compared to LP_C37, LT_C3 + LP_C46 and LP C37 + UMP reduced the peak stress level at the intervertebral disc by at most 2-fold as well as the peak strain level of the facet joint capsule by 2–3-fold. All these findings were well correlated with the result of clinical studies comparing modified laminoplasty and classic laminoplasty. Conclusions: Modified muscle-preserving laminoplasty is superior to classic laminoplasty due to the biomechanical effect of the posterior musculature reconstruction, with a retained postoperative ROM and loading response levels of the functional spinal units. More motion-sparing is beneficial for increasing cervical stability, which probably accelerates the recovery of postoperative neck movement and reduces the risk of the complication for eventual kyphosis and axial pain. Surgeons are encouraged to make every effort to preserve the attachment of the C2 whenever feasible in laminoplasty.